Difficulties Encountered In the Conduct of Student Researches - Micabalo, Kingie; Cano, Jesszon; Montilla, Ryan; Tan, Arsenio Robert; Navarro, June Ace (JPAIR Institutional Research, 2020)
Research is a mission for trust with the assistance of study, acknowledgment, association, and preliminaries in the journey for information through the goal and proficient methodology to discover answers for an issue. The examination decides and breaks down the degree of appraisal seen by the understudies regarding the complexity and significance of the research. The examination respondents were the 252 understudies from Marketing and Human Resource Management courses utilizing the descriptive survey method as a research instrument on a simple random sampling. Frequency and simple percentages, and Mode were used to summarize, separate, and unravel the information. The discovery uncovered that understudies perceived the importance of research undertakings. However, the investigation revealed that acquainting with different investigations in regions identified with research is a complex thing during the proposal. Ampleness of information in estimating apparatuses (insights) to evaluate and examine research information is the complex part of conducting the research. Lastly, introducing thoughts intelligently, legitimately, plainly, and carefully is the complex part of writing the research paper. The study concluded that constructive alignment between teaching and learning in the proposal stage, conducting the research, and writing the paper must be practiced to ensure the stronger realization of students’ journey and output in doing research.
Keywords: Education; Teaching and learning; research; descriptive study; Mandaue City; Philippine